Dagny Juel o g Stanisław Przybyszewski - ’kulturarbeidere’ for Norgeog Polen - Sawicka, Aleksandra (Folia Scandinavica Posnaniensia, 2017)
The article is an attempt to present Dagny Juel and Stanisław Przybyszewski’s role in strenghtening the cultural links between Norway and Poland. The Przybyszewskis’ contacts with Edvard Munch, Gustav Vigeland and other Scandinavian artists from the “Zum schwarzen Ferkel” tavern in Berlin and the Kristiania (Oslo) circles have been portrayed. The couple, promoting links among the bohemian artists as well as through their translation work, exerted a paramount impact on shaping the cultural life of Central Europe. What is more, the life of those extraordinary personalities proved to be a source of inspiration for numerous Polish and Norwegian artists. The article includes information about paintings and sculptures presenting Dagny Juel and her husband.